THE SIGNIFICANCE OF MAGNETIC RESONANCE IMAGING IN ADDITION TO COMPUTER TOMOGRAPHY IN THE EVALUATION OF CERVICAL SPINE TRAUMAS IN PATIENTS WITH BLUNT TRAUMA - Gasimzade, G.Sh. (World of Medicine and Biology, 2021)
Missed spinal injuries can be fatal, leading to paralysis and lifelong disability. The possibility of avoiding missed trauma was determined in 78 patients with blunt trauma, the mean age was 43.1±8.14 years. The patients underwent CT and MRI. Statistical analysis was conducted using computer software package SPSS. Transport injuries were more common – 87.2 %. In 16.7 % of cases, CT revealed concomitant ossification of the posterior longitudinal ligament. The chance of finding bilateral facet dislocation was 0.238 for hernia using MRI, 0.026 for CT, 0.857 and 0.114 for epidural hematoma, respectively. The chance of finding unilateral facet dislocation with bone edema without fracture was 1.516 on MRI and 0.182 on CT. Bone anatomy is better visualized on CT, disc herniation and hemorrhage on MRI. When evaluating spinal injuries, the use of CT and MRI is recommended.
Keywords: blunt trauma; cervical spine; computed tomography; magnetic resonance imaging; injury mechanism; chance ratio